Measurement of Shrinkage and Cracking in Lyophilized Amorphous Cakes, Part 3: Hydrophobic Vials and the Question of Adhesion - Ullrich, Sabine; Seyferth, Stefan; Lee, Geoffrey (Journal of Pharmaceutical Sciences, 2015)
The importance of cake adhesion to the inside vial wall during lyophilization of amorphous trehalose cakes was determined by using hydrophobized vials. The degrees of cake shrinkage and cracking were determined independently by photographic imaging of the cake top surface in a dark cell. Additionally, measurements with microcomputed tomography were performed. Adhesion is found to be a determining factor in both cake shrinkage and cracking. The correlation between cake detachment from the vial inner wall and trehalose concentration indicates that adhesion of the frozen solute phase is a determining factor in shrinkage. The hydrophobized vials give reduced cracking at trehalose concentrations of up to 15%. The reduced wetting of the hydrophobized inside vial wall gives a planar cake topography with a uniform distribution of cracks within the cake.
UnivIS-Import:2015-07-08:Pub.2015.nat.dchph.lphte.measur_6
Keywords: lyophilization; amorphous; contact angles; materials science; excipients